EXPERIMENTAL EVALUATION OF DIETS FOR CULTURE OF A POTENTIAL LIVE FEED, Euplotes Sp. (PROTOZOA, CILIOPHORA) - BALAMURALI, R. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Ciliate protozoans such as Euplotes which are seen among the mass cultures of rotifers have the potential as a live feed for larvae and juveniles of the aquaculture species in hatchery operations. Free living ciliates are potential natural food of many fish larvae because of their smaller size. To obtain the culture of Euplotes sp., four diets were tested 1) Microalgae, Nannochloropsis oculata, 2) Isochrysis galbana, 3) Equal proportion of N. oculata and I. galbana and 4) Baker's yeast (Saccharomyces cerevisiae). The ciliates were inoculated at a concentration of 50 cells mL-1. On day 5, Euplotes density reached highest in the groups fed the baker's yeast (14600.00 ± 409.88 cells mL-1) in comparison with the other three media N. oculata (933.3 ± 659.29 cells mL-1 ); I. galbana + N. oculata (966.67 ± 806.64 cells mL-1 ) and I. galbana (333.33 ± 103.28 cells mL-1 ). Six days culture is crucial because most of the marine fish larvae start their feeding by 5-7 days of post hatching. It was observed from the results that Baker's yeast is highly significant (P<0.01) diet of Euplotes sp. in mass culture.